Teknologi Percepatan Pertumbuhan Bibit Duku (Lansium domesticum Corr) melalui Aplikasi Fungi Mikoriza Arbuskular [Accelerating The Growth of Duku Seedlings (Lansium domesticum Corr) through the Application of Arbuscular Mycorrhizal Fungi)] - Lizawati LIZAWATI; Elis KARTIKA; Elly Indra SWARI; Zul Fahri GANI (Biospecies, 2015)
The research investigated the influence of four isolates of arbuscular mycorrhizal fungi(AMF) on the growth of duku seedlings. The research used randomized block design with onefactor of some isolates AMF: Glomus-sp 3, 6, 15, and 16 at a dose of 20 g per polybag. The resultsshowed that inoculation of AMF isolates increase the canopy and root growth of the dukuseedlings. Duku seedlings inoculated with mycorrhiza showed higher plant height, stem diameter,dry weight, secondary roots number and length, than the control. Furthermore, mycorrhizalinoculation increased the absorption of nutrients (Phosphor) in the leaves of duku seedlings. Rootstaining results showed that AMF colonization in the duku roots only indicate hyphae; the otherstructures (vesicles, arbuscular and spores) were not detected.